The Effects of Action, Normality, and Decision Carefulness on Anticipated Regret: Evidence for a Broad Mediating Role of Decision Justifiability - REB, Jochen (Institutional Knowledge at Singapore Management University, 2007)
In three studies we examined the effects of action/inaction, social normality (i.e., how typical the decision is in one’s social environment) and decision process carefulness on anticipated regret. Whereas past research has drawn on norm theory (Kahneman & Miller, 1986) to emphasize the role of mutability in (anticipated) regret, the present studies highlight the important role of perceptions of decision justifiability (Connolly & Zeelenberg, 2002). Study 1 replicated earlier findings showing greater anticipated regret when behavior was abnormal, but perceived justifiability mediated the effect. Study 2 showed that anticipated regret was higher for careless than for careful decisions; perceived decision justifiability again mediated the effect. Study 3 found that, when both carefulness and normality information was provided, only the former affected anticipated regret, again mediated by perceived justifiability. Decision justification theory thus appears to provide a better account of anticipated regret intensity in this context than does norm theory.